An analytical method for a pile-stabilised slope considering soil anisotropy. Issue 1 (16th February 2020) - Zhuang, Yan; Cui, Xiaoyan; Dai, Guoliang; Geng, Xueyu; Li, Shuai
Abstract : The use of stabilising piles is an effective method of reinforcing a slope against landslides. Soil arching between the piles promotes more load transfer into the piles, improving the safety of a slope. However, few analytical solutions have been proposed for assessing the safety of an anisotropic slope with soil arching between stabilising piles, especially in most current design procedures. Based on British standard BS8006, an analytical method was proposed to evaluate the stability of a stabilising-pile-reinforced slope where the anisotropy of soil strength and horizontal soil-arching effect were taken into account. A field case was then used to compare with the results calculated by the proposed analytical method, with the differences in the range of approximately 0.6−8.9%. To validate the proposed analytical method, a three-dimensional numerical simulation technique considering the anisotropy of soils was conducted, in which variation of soil cohesion with depth and direction of principal stress was introduced into the numerical analysis. It was found that the safety factors predicted by the numerical simulation agreed well with those derived by the proposed analytical method, with the differences in the range of 0.7−17%. The safety factor was found to decrease with increasing the anisotropic coefficient, and increased with higher effective cohesion and effective friction angle.